Analisis Penilaian Kinerja Karyawan PT Prima Indo Energi - Tazkia, Fahara; Jaelani, Dede (Jurnal Online Manajemen ELPEI, 2024)
This research aims to analyze the implementation of employee performance appraisal at PT Prima Indo Energi with a focus on objectives, methods and results. This research uses a qualitative method with a case study design. The research method involves a review of the purpose of performance appraisal, the methods used, and the process and frequency of employee evaluation. PT Prima Indo Energi implements performance appraisals with the main aim of improving employee performance. The assessment method is holistic and diverse, involving evaluation by direct superiors, colleagues, subordinates, self-assessment, and achievement of work targets. The assessment frequency is carried out regularly every six months and is unscheduled to capture the dynamics of employee performance in unexpected situations. The appraisal process involves comprehensive steps, from goal setting to employee feedback, with active employee participation in the entire process. The implementation of performance assessments at PT Prima Indo Energi creates a comprehensive and sustainable framework. The purpose of assessment is not only limited to evaluation, but also to employee development. Holistic and diverse assessment methods, structured evaluation frequency, and active employee participation form a strong foundation for effective performance management.